Targeting programmed cell death via active ingredients from natural plants: a promising approach to cancer therapy - Li, Qian; Tong, Yan; Chen, Jianxiang; Xie, Tian (Frontiers in Pharmacology, 2024)
Cancer is a serious public health problem in humans, and prevention and control strategies are still necessary. Therefore, the development of new therapeutic drugs is urgently needed. Targeting programmed cell death, particularly via the induction of cancer cell apoptosis, is one of the cancer treatment approaches employed. Recently, an increasing number of studies have shown that compounds from natural plants can target programmed cell death and kill cancer cells, laying the groundwork for use in future anticancer treatments. In this review, we focus on the latest research progress on the role and mechanism of natural plant active ingredients in different forms of programmed cell death, such as apoptosis, autophagy, necroptosis, ferroptosis, and pyroptosis, to provide a strong theoretical basis for the clinical development of antitumor drugs.